Wildlife existence and potential threats in Pelangi Forest Biosite of Ijen Geopark, East Java, Indonesia - ARIF MOHAMMAD SIDDIQ; AGUNG SIH KURNIANTO; HARI SULISTIYOWATI; MUHAMAD TENTREM WIJAYA; TRI RATNASARI; NILASARI DEWI; EVA TYAS UTAMI; TANTRI RARAS AYUNINGTYAS (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Siddiq AM, Kurnianto AS, Sulistiyowati H, Wijaya MT, Ratnasari T, Dewi N, Utami ET, Ayuningtyas TR. 2024. Wildlife existence and potential threats in Pelangi Forest Biosite of Ijen Geopark, East Java, Indonesia. Biodiversitas 25: 4487-4497. A comprehensive study of the diverse wildlife and potential threats at the Pelangi Forest Biosite (Rainbow Forest Biosite, RFB) of Ijen Geopark, East Java, Indonesia was conducted in May 2023. Bird and primate observations were carried out using the point count method, while herpetofauna observation was conducted using the Visual Encounter Survey (VES). Data collection on potential threats to community activities in the RFB used a questionnaire survey method. Data analysis used the Diversity Index (H’), Existence factor (Ef), and scale-Likert for potential threats. The Pelangi Forest is home to an impressive 62 wildlife species, including six amphibian species, nine reptile species, 46 bird species, and one primate species. The value of wildlife species diversity in RFB, calculated using the Shannon-Wiener index, is remarkably high (H= 3.48). The wildlife species in the Pelangi Forest had an average existence value of 41.94%, indicating a moderate uniqueness level, with the Javan lutung (Trachypithecus auratus (É.Geoffroy Saint-Hilaire, 1812)) standing out with the highest Ef value (80%). According to Likert-scale analysis, potential threats to biodiversity in the RFB of Ijen Geopark are relatively low (23.54%). However, some crucial notes for evaluating the conservation plan, namely the illegal poaching or hunting of wildlife species, such as birds and large mammals, still occur. Therefore, implementing education-based tourism, such as birdwatching or wildlife observation, can increase awareness and knowledge about conservation for tourists and society.